2011
DOI: 10.1021/bm101562v
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Imprinted PHEMA-Hydrogels for Ocular Delivery of Carbonic Anhydrase Inhibitor Drugs

Abstract: Hydrogels with high affinity for carbonic anhydrase (CA) inhibitor drugs have been designed trying to mimic the active site of the physiological metallo-enzyme receptor. Using hydroxyethyl methacrylate (HEMA) as the backbone component, zinc methacrylate, 1- or 4-vinylimidazole (1VI or 4VI), and N-hydroxyethyl acrylamide (HEAA) were combined at different ratios to reproduce in the hydrogels the cone-shaped cavity of the CA, which contains a Zn(2+) ion coordinated to three histidine residues. 4VI resembles histi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 49 publications
0
63
0
1
Order By: Relevance
“…Prolonged release on the corneal surface of hydrophilic drugs might be better achieved by means of contact lenses or hydrogel films that bear functional moieties suitable for interacting with the drug molecules [15]. Thus, compared with the biomimetic/imprinted contact lenses [15,50], poloxamine micelles may offer higher initial levels of ETOX at the lachrymal fluid; the greater concentration gradient facilitating the passing through the cornea of this high permeability drug. Subsequent application of ETOX-medicated contact lenses may enable the attainment of long-term drug levels.…”
Section: ð3:2þmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged release on the corneal surface of hydrophilic drugs might be better achieved by means of contact lenses or hydrogel films that bear functional moieties suitable for interacting with the drug molecules [15]. Thus, compared with the biomimetic/imprinted contact lenses [15,50], poloxamine micelles may offer higher initial levels of ETOX at the lachrymal fluid; the greater concentration gradient facilitating the passing through the cornea of this high permeability drug. Subsequent application of ETOX-medicated contact lenses may enable the attainment of long-term drug levels.…”
Section: ð3:2þmentioning
confidence: 99%
“…On the other hand, it was shown that ETOX can be solubilized by forming inclusion complexes with cyclodextrin derivatives and that topically active formulations which combine ETOX and timolol can be thus prepared [13,14]. More recently, biomimetic contact lenses capable of loading ETOX and of controlling the drug release were prepared with the intention of prolonging the contact time between the drug and the eye and enhancing the ocular bioavailability [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to modify the conventional contact lenses to improve their drug loading and release (16,52,(60)(61)(62)(63)(64)(65). The use of a device from which a drug may diffuse can improve the contact time of the drug with its target tissue.…”
Section: Soft Contact Lenses For Ocular Drug Delivery and Strategies mentioning
confidence: 99%
“…Vitamin E loading proved to be very effective in increasing release duration of lidocaine, CyA, timolol, levofloxacin, chlorhexidine, dorzolamine, dexpantenol, betaine, dexamethasone and betamethasone, from hours to several days. [32][33][34][35][36][37] Research on dry eye management has been increasingly focusing on the inflammatory aspect and CyA was FDA approved to treat moderate-to-severe dry eye disease. SHCLs were able to keep CyA delivery rates within therapeutic levels for 14 days.…”
mentioning
confidence: 99%